New low-cost magnifying device for temporal bone laboratory - Vittorio Rinaldi; Manuele Casale; Antonio Moffa; Giovanni Mancini; Daniela Carioli; Didier Portmann; Michele Cassano; Lorenzo Pignataro (Journal of Otology)
Temporal bone dissection has important role in educating and training oto and skull base surgeons. Mounting of a temporal bone laboratory is expensive. A dedicated magnifying system, such as a surgical microscope or an endoscopic equipment, represents one of the most significant costs. The aim of this study is to test and demonstrate the utility of a commercial USB as a low-cost solution to equip the laboratory with a good magnifying system and illumination. Keywords: Temporal bone dissection, Temporal bone laboratory, Temporal bone surgical technique training